Clinical supervision of allied health professionals in country South Australia: A mixed methods pilot study. (27th August 2015) - Kumar, Saravana; Osborne, Kate; Lehmann, Tanya
Abstract Introduction Recent times have witnessed dramatic changes in health care with overt recognition for quality and safety to underpin health care service delivery. In addition to systems‐wide focus, the importance of supporting and mentoring people delivering the care has also been recognised. This can be achieved through quality clinical supervision. In 2010, Country Health South Australia Local Health Network developed a holistic allied health clinical governance structure, which was implemented in 2011. Objective This research reports on emergent findings from the evaluation of the clinical governance structure, which included mandating clinical supervision for all allied health staff. Methods A mixed method approach was chosen with evaluation of the impact of clinical supervision undertaken by a psychometrically sound instrument (Manchester Clinical Supervision Scale 26‐item version), collected through an anonymous online survey and qualitative data collected through semistructured interviews and focus groups. Results Overall, 189 allied health professionals responded to the survey. Survey responses indicated allied health professionals recognised the importance of and valued receiving clinical supervision (normative domain), had levels of trust and rapport with, and were supported by supervisors (restorative domain) and positively affected their delivery of care and improvement in skills (formative domain). Qualitative data identified enablers such as profession specific gains, improved opportunities and consistency for clinical supervision and barriers such as persistent organisational issues, lack of clarity (delineation of roles) and communication issues. Conclusion The findings from this research highlight that while clinical supervision has an important role to play, it is not a panacea for all the ills of the health care system.